2017
DOI: 10.1016/j.jcm.2017.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Static and Dynamic Balance Tests in Single and Dual Task Conditions in Participants With Nonspecific Chronic Low Back Pain

Abstract: It seems that the static and dynamic balance performance under dual task conditions (excluding the Modified Star Excursion Balance Test) was impaired in each group. Dual tasking did not differ between nonspecific chronic low back pain participants with low level of pain and disability compared with healthy participants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
11
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 31 publications
4
11
0
1
Order By: Relevance
“…Previous studies have reported that DT diminished physical performance in both healthy [31] and chronic pain patients. [32] Our results are consistent with those observed by de Gier et al [14] who observed physical performance reduction caused by adding a secondary task. Furthermore, Hemmati et al [32] showed that physical performance was impaired under DT conditions in low back pain patients.…”
Section: Discussionsupporting
confidence: 93%
“…Previous studies have reported that DT diminished physical performance in both healthy [31] and chronic pain patients. [32] Our results are consistent with those observed by de Gier et al [14] who observed physical performance reduction caused by adding a secondary task. Furthermore, Hemmati et al [32] showed that physical performance was impaired under DT conditions in low back pain patients.…”
Section: Discussionsupporting
confidence: 93%
“…However, the R 2 value for low back pain in relation to lateral muscular asymmetry is 14% which indicates a weak strength of the relationship between the variables. This finding coincides with prior studies that suggest postural control is not associated with back pain [ 6 - 9 ]. However, the positive coefficient of the best fit line and low R 2 value demonstrated in this study contrasts a study showing poorer postural control in patients with back pain [ 10 ].…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, there is unlikely an association between lateral load tolerance and back pain. This finding coincides with prior studies that suggest postural control is not associated with back pain [ 6 - 9 ].…”
Section: Discussionsupporting
confidence: 92%
“…Although the original SEBT consists of eight directions, conventional testing procedures have adopted a modified version of the test, using the anterior, posteromedial, and posterolateral directions (Plisky et al, 2006) due to its high level of representativeness (Hertel et al, 2006). The MSEBT version has been widely used in sports as injury-prevention screening tool (Gkrilias et al, 2018) and to evaluate dynamic balance (Hemmati et al, 2017;Denehey et al, 2018).…”
Section: Testing Apparatusmentioning
confidence: 99%